ChemInform Abstract: Aromaticity and Conjugation in 1, 2‐Benzoquinone Valence Isomers and Congeners. Issue 24 (June 2015) - Balaban, Alexandru T.; Greer, Alexander; Liebman, Joel F.
Abstract: Review: 225 refs.